Does Platform Owner’s Entry Crowd Out Innovation? Evidence from Google Photos - Foerderer, Jens; Kude, Thomas; Mithas, Sunil; Heinzl, Armin (Information Systems Research, 2018)
We study how platform owners’ decision to enter complementary markets affects innovation in the ecosystem surrounding the platform. Despite heated debates on the behavior of platform owners toward complementors, relatively little is known about the mechanisms linking platform owners’ entry and complementary innovation. We exploit Google’s 2015 entry into the market for photography apps on its own Android platform as a quasi-experiment. We conclude based on our analyses of a time-series panel of 6,620 apps that Google’s entry was associated with a substantial increase in complementary innovation. We estimate that the entry caused a 9.6% increase in the likelihood of major updates for apps affected by Google’s entry, compared to similar but not affected apps. Further analyses suggest that Google’s entry triggered complementary innovation because of the increased consumer attention for photography apps, instead of competitive “racing” or “Red Queen” effects. This attention spillover effect was particularly pronounced for larger and more diversified complementors. The study advances our understanding of the effects of platform owner’s entry, explicates the complex mechanisms that shape complementary innovation, and adds empirical evidence to the debate on regulating platforms. The online appendix is available at https://doi.org/10.1287/isre.2018.0787 .